Inhibition of Plasmodium falciparum Hsp70-Hop partnership by 2-phenylthynesulfonamide - Muthelo, Tshifhiwa; Mulaudzi, Vhahangwele; Netshishivhe, Munei; Dongola, Tendamudzimu Harmfree; Kok, Michelle; Makumire, Stanley; de Villiers, Marianne; Burger, Adélle; Zininga, Tawanda; Shonhai, Addmore (Frontiers in Molecular Biosciences, 2022)
Plasmodium falciparum Hsp70-1 (PfHsp70-1; PF3D7_0818900) and PfHsp90 (PF3D7_0708400) are essential cytosol localized chaperones of the malaria parasite. The two chaperones form a functional complex via the adaptor protein, Hsp90-Hsp70 organising protein (PfHop [PF3D7_1434300]), which modulates the interaction of PfHsp70-1 and PfHsp90 through its tetracopeptide repeat (TPR) domains in a nucleotide-dependent fashion. On the other hand, PfHsp70-1 and PfHsp90 possess C-terminal EEVD and MEEVD motifs, respectively, which are crucial for their interaction with PfHop. By coordinating the cooperation of these two chaperones, PfHop plays an important role in the survival of the malaria parasite. 2-Phenylthynesulfonamide (PES) is a known anti-cancer agent whose mode of action is to inhibit Hsp70 function. In the current study, we explored the antiplasmodial activity of PES and investigated its capability to target the functions of PfHsp70-1 and its co-chaperone, PfHop. PES exhibited modest antiplasmodial activity (IC50 of 38.7 ± 0.7 µM). Furthermore, using surface plasmon resonance (SPR) analysis, we demonstrated that PES was capable of binding recombinant forms of both PfHsp70-1 and PfHop. Using limited proteolysis and intrinsic fluorescence-based analysis, we showed that PES induces conformational changes in PfHsp70-1 and PfHop. In addition, we demonstrated that PES inhibits the chaperone function of PfHsp70-1. Consequently, PES abrogated the association of the two proteins in vitro. Our study findings contribute to the growing efforts to expand the arsenal of potential antimalarial compounds in the wake of growing parasite resistance against currently used drugs.